The Moderating Effects of Personality Traits on Stressor--Symptom Contingencies in Borderline Personality Disorder - Miskewicz, Kelly (Wake Forest University, 2014)
The purpose of this study was to reveal the way in which personality traits moderate contingent relationships among proximal situational stressors and symptoms of Borderline Personality Disorder (BPD). The main question of interest was whether personality traits explain why people with BPD experience stronger symptom reactions to proximal situational stressors, relative to people without BPD. Two hundred and thirty one (n = 231) participants, including 67 people with BPD, reported on their situational context and symptom experience five times per day for two weeks, and also completed a personality questionnaire. Multilevel modeling was used to examine the associations among personality traits and frequency of stressor experience, symptom intensity, and symptomatic reactivity to proximal stressors. The mediating effects of personality traits on the moderating effect of BPD diagnosis were also examined. Generally, results revealed that personality traits do not explain why people with BPD experience more frequent stressors, more intense symptoms, and heightened reactivity to stressors. It is concluded that traits are not a primary mechanism underlying contingencies in BPD. There are likely other aspect(s) of the disorder that account for stressor experience, symptom intensity, and symptomatic reactivity to stressors. Study limitations and future directions are discussed.
Keywords: Borderline Personality Disorder; Contingencies; Symptom; Traits